Developing International Migrant Labors Pattern: The Case of Tourism and Hospitality Industry - Mohd Shariff, Nurhazani; Zainol Abidin, Azlan (International Review of Management and Marketing, 2017)
The needs of international migrant labors to fill in the shortages of labor in various sectors have created several advantages. Further, the employment of international migrant labors in tourism and hospitality industry presents a series of opportunities alongside challenges for stakeholders such as migrants, employers and host communities. The international migrant labors can assist in making market entry mode and marketing strategies selection decisions. A study was conducted to develop international migrant labors pattern in the case of tourism and hospitality industry in Langkawi, Malaysia. The pattern of international migrant labors is presented through their various socio-demographic profiles. It is noted in the pattern that majority of the international migrant labors is male within the range of 31 – 50 years old and only few of them are still single. In fact, most of them are from Thailand. The pattern shows similar results for the female international migrant labors. The pattern also highlights that the international migrant labors for both male and female graduated from university, however, only few of the females possessed the degree certificate. Interestingly both male and female international migrant labors can communicate good English. This pattern would assist the tourism and hospitality industry to plan a strategic recruitment process concerning the international migrant labors. By taking into account their socio-demographic profiles would contribute to the segmentation of the international migrant labors for future recruitment. Keywords: International migrant labors, pattern, employment, tourism and hospitality industry JEL Classifications: F22, J21, Z31